Ai and the future of banking - Boobier, Tony (Gildan Audio, 2020)
An industry-specific guide to the applications of Advanced Analytics and AI to the banking industryArtificial Intelligence (AI) technologies help organizations to get smarter and more effective over time-ultimately responding to, learning from, and interacting with human voices. It is predicted that by 2025, half of all businesses will be using these intelligent, self-learning systems. Across its entire breadth and depth, the banking industry is at the forefront of investigating Advanced Analytics and AI technology for use in a broad range of applications, such as customer analytics and providing wealth advice for clients. AI and the Future of Banking provides new and established banking industry professionals with essential information on the implications of data and analytics on their roles, responsibilities, and personal career development.This accessible guide is designed to be easily understood by any banking professional with limited or no IT background. Chapters focus on practical guidance on the use of analytics to improve operational effectiveness, customer retention, and finance and risk management. Theory and published case studies are clearly explained, while considerations such as operating costs, regulation, and market saturation are discussed in real-world context.